A kindred with cerebellar ataxia and thermoanalgesia. Issue 5 (18th August 2008) - Genis, D; Ferrer, I; Valls Solé, J; Corral, J; Volpini, V; San Nicolás, H; Gich, J; Ramió-Torrentà, L; Ferrándiz, M; Puig, J; Márquez, F
Abstract : Objective: To characterise the clinical, neurophysiological, neuropathological and genetic features of a family with cerebellar autosomal dominant ataxia. Design: Patients were submitted to clinical, neuroradiological and neurophysiological examinations. Molecular studies were undertaken to exclude SCAs 1–3, 6–8, 12 and 17. Studies were performed to rule out linkage to SCA4 on chromosome 16, and for all still uncharacterised SCA loci. Neuropathological examination of the proband was performed with immunocytochemistry. Results: These patients presented a late onset cerebellar ataxia with thermoanalgesia and deep sensory loss. Unlike in SCA4, reflexes were preserved. MRI revealed cerebellar, medullar and spinal cord atrophy. Neurophysiological studies showed absence or marked reduction of the sensory nerve action potentials and somatosensory evoked potentials in lower and upper limbs but preservation of the soleus H reflex. No triplet repeat expansion mutations in the studied SCA genes were identified. Our studies ruled out linkage of the disease to the SCA4 locus on chromosome 16 and the remaining reported SCA loci. The neuropathological study of the proband revealed severe loss of Purkinje cells and dentate neurons. The inferior olive and lower cranial nerve nuclei also showed extensive cell loss. Posterior columns and spinocerebellar tracts were demyelinated. Ubiquitin immunoreactive intranuclear inclusions were absent. Conclusion: This kind of cerebellar ataxia, associated with thermoanalgesia as well as deep sensory loss with retained reflexes, does not associate to any known SCA loci. Therefore, we identify and describe a new form of late onset dominant spinocerebellar ataxia.